2020
DOI: 10.1590/1413-812320202510.2.29452020
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome Respiratória Aguda Grave em Pernambuco: comparativo dos padrões antes e durante a pandemia de COVID-19

Abstract: Resumo Foi analisado o padrão da Síndrome Respiratória Aguda Grave (SRAG) em Pernambuco antes e durante período pandêmico da COVID-19. Estudo ecológico, de janeiro a junho de 2015 a 2019 (período pré-pandemia) e 01 de janeiro a 15 de junho de 2020, período que contempla parte inicial da pandemia. Taxas de detecção por município e Regional de Saúde de residência foram calculadas e, por meio da razão de risco, a dinâmica espacial da SRAG foi estimada. Na pré-pandemia ocorreram 5.617 casos de SRAG, 187 casos/mês … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
1
7
0
5
Order By: Relevance
“…Some studies demonstrated that the MHDI factor is interconnected to the occurrence of cases, with the number of deaths and confirmed cases being inversely proportional to the MHDI [57,58]. Although small, medium and large municipalities have different means of MHDI-0.7031, 0.7041 and 1.765 respectively, we did not detect interference of this macro determinant in the occurrence of cases, probably because the data are restricted to the initial stage of pandemic occurrence [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that the MHDI factor is interconnected to the occurrence of cases, with the number of deaths and confirmed cases being inversely proportional to the MHDI [57,58]. Although small, medium and large municipalities have different means of MHDI-0.7031, 0.7041 and 1.765 respectively, we did not detect interference of this macro determinant in the occurrence of cases, probably because the data are restricted to the initial stage of pandemic occurrence [20].…”
Section: Discussionmentioning
confidence: 99%
“…No início de março, foi publicado o primeiro Boletim Epidemiológico pernambucano, havendo atualizações diárias até o presente dia. Nestes boletins, constam informações importantes sobre casos suspeitos e confirmados, óbitos, recuperação dos pacientes, atualização de notas técnicas, assim como os dados da vacinação atualmente (Silva et al, 2020c;Ximenes et. al., 2021).…”
Section: Resultsunclassified
“…5 For the present study, the SARS case registry was used as a proxy (representative) of COVID-19 incidence, which had been justified through other studies using SARS data during the pandemic period. 8,9,10 Furthermore, with the pandemic, the reinforcement of the SARS surveillance system represented an important step forward for public health, in the light of the epidemiology of respiratory agents. 11 The Brazilian Institute for Geography and Statistics (Instituto Brasileiro de Geografia e Estatística, IBGE) was used as a source for data referring to the regions of influence (Regiões de Influência das Cidades, REGIC) 12,13 and accessibility of the municipalities of Acre.…”
Section: Methodsmentioning
confidence: 99%